Between the classical Mu'tazilites and neo-Mu'tazilites: an analysis of Harun Nasution’s modern Islamic thought in Indonesia - Awang Abd Rahman, Amilah (Journal of Nusantara Studies (JONUS), 2020)
Lately, the classical schools of Islamic theology are generally associated with various modern movements such as Neo-Kharijites and Neo-Mu'tazilites especially in terms of their negative influence. This paper aims at critically analyzing the way in which modern Muslim scholars claim the legacy of the classical Mu‘tazilite school. It specifically offers a critical overview of the spirit and contents of both early Islamic movements. It is attempted to draw a more objective picture of the classical Mu‘tazilite school, based on their primary sources. The Indonesian Harun Nasution is taken as an example of a Neo-Mu‘tazilite scholar. This paper argues that the original Mu’tazilite spirit is not accurately represented by Harun Nasution. The Mu‘tazilite was the first theological school who tried to defend and preserve the original teachings of Islam in the face of the many challenges of their time. Today, the Mu‘tazilite school is often misrepresented by portraying it as a purely rationalistic school and liberal thought. It is the view of the author that the misrepresentation of the Mu‘tazilite school as being a radical school of thought that propagated liberal society solely guided by reason, will bring bad consequence to the understanding and development of Muslim society in general. It can be either giving opportunity to the rise of liberal society with the claim of past root of the history of Muslims as occurred in Nasution’s case or rejecting reason from being important source of knowledge acknowledged by Islam.